Hypersensitivity to Catabolite Repression in the l-Arabinose Operon of Escherichia coli B/r Is trans Acting - Sheppard, David E. (1976)
Mutations causing hypersensitivity to catabolite repression have been assigned to gene araC (activator protein) by complementation analysis. The araO (operator region) is non-essential for catabolite repression.